To commit or not to commit: A health insurance monopoly with variable quality and uncertain types of individuals - Mathias Kifmann (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1997)
This paper examines the trade-off between risk allocation and quality supply for an insurance monopolist when individuals face two kinds of risk related to health. First, they may suffer an ordinary monetary loss. Second, they are subject to uncertain premiums because their type may change. We assume that neither quality of insurance service,nor the individual type is verifiable in front of a court. We show that no-commitment is a necessary condition for the efficient supply of unverifiable quality while the insurance of premium risk requires commitment. Profit-maximizing contracts may involve full, partial or no- commitment. Risk allocation or quality supply is inefficient.
Keywords: D80; I10; 330; health insurance; premium risk; unverifiable quality; commitment